2017
DOI: 10.1007/s40858-017-0153-5
|View full text |Cite
|
Sign up to set email alerts
|

Emulsions of essential oils and aloe polysaccharides: Antimicrobial activity and resistance inducer potential against Xanthomonas fragariae

Abstract: Bacterial angular leaf spot disease (Xanthomonas fragariae) is an important strawberry disease and responsible for significant yield losses. The efficacy of emulsions containing tea tree or palmarosa essential oils (EO) against angular leaf spot, seeking to elucidate their mode of action, was evaluated in this study. Tea tree or palmarosa EO were added in an aqueous suspension of aloe polysaccharide (AP) and tea tree EO emulsion (TAP) and palmarosa EO microemulsion (PAP) were obtained. The antimicrobial potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…They found that from all of the tested alcoholic and aqueous extracts, A. vera showed the strongest activity against E. coli and S. aureus . What is more, aloe polysaccharides were used in tea tree or palmarosa essential oil combinations as a natural strategy against Xanthomonas fragariae (bacterial angular leaf spot disease, which is an important strawberry disease responsible for significant yield losses) [ 138 ]. It was found that these preparations reduce disease severity and activate plant defenses, and that Aloe polysaccharides alone reduced X. fragariae growth by up to 44%.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…They found that from all of the tested alcoholic and aqueous extracts, A. vera showed the strongest activity against E. coli and S. aureus . What is more, aloe polysaccharides were used in tea tree or palmarosa essential oil combinations as a natural strategy against Xanthomonas fragariae (bacterial angular leaf spot disease, which is an important strawberry disease responsible for significant yield losses) [ 138 ]. It was found that these preparations reduce disease severity and activate plant defenses, and that Aloe polysaccharides alone reduced X. fragariae growth by up to 44%.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Polysaccharides are a kind of carbohydrate with high molecular weight, which represent a major class of bioactive molecules derived from microorganisms, animals, or plants [1]. Polysaccharides are extensively used in various healthcare products and medicines because of their notable and excellent bioactivities, such as antimicrobial [2], antitumor [3], antiviral [4], and antioxidant activities [5]. In addition, polysaccharides are among the natural biopolymers found on Earth [6], which are widely used as biomaterials for wound healing [7], drug delivery [8] and tissue engineering [9].…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides are monosaccharides polymers joined by glycosidic bonds. They are reported to have antioxidant, antibacterial, antiviral, and antitumor properties, making them essential products in the pharmaceutical, food, and feed as well as cosmetic industries [ 34 , 35 , 36 , 37 ]. The polysaccharide content obtained from the various extracts is presented in Figure 2 A.…”
Section: Resultsmentioning
confidence: 99%